Chiari Type I Malformation and Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Four children with epilepsy, ranging in age from 8 to 15 years, and diagnosed with Chiari type I malformation by brain magnetic resonance imaging (MRI), are reported from La Sapienza University, Rome, Italy.